Deoxypodophyllotoxin Inhibits Non-Small Cell Lung Cancer Cell Growth by Reducing HIF-1α-Mediated Glycolysis - Yang, Yuping; Liu, Lingling; Sun, Jinghui; Wang, Shu; Yang, Zhongyuan; Li, Honghui; Huang, Na; Zhao, Wei (Frontiers in Oncology, 2021)
Cancer cell proliferation is a metabolically demanding process that requires high rate of glycolysis to support anabolic growth. Deoxypodophyllotoxin (DPT) is a natural flavonolignan with various pharmacological activities, including antitumoreffect. However, whether DPT affects the metabolic reprogramming of cancer cells is unknown. The purpose of this study is to investigate the role of DPT on non-small cell lung cancer (NSCLC) and to explore whether HIF-1α-mediated glycolysis is involved in its mechanism of action.The level of HIF-1α mRNA and protein in NSCLC cells following DPT treatment was detected using qRT-PCR and western blotting, respectively. Cell Counting Kit-8 (CCK-8) and caspase-3 activity assays were performed to analyse cell proliferation and apoptosis. The underlying molecular mechanism was identified by dual luciferase assay, Western blotting, qRT-PCR, glucose consumption, lactate production, and immunoprecipitation. A murine NSCLC model was used to clarify the effect of DPT treatment on tumor cell proliferation. Our findings showed that DPT treatmentinhibited NSCLC cell growth in a dose- and time-dependent manner. Further analysis suggested that DPT treatment inhibited HIF-1α signalling pathway by Parkin-mediated protein degradation in NSCLC cells. DPT treatment significantly decreased glucose consumption and lactate production.In addition, DPT treatment reduced the expression of HIF-1α target genes, including GLUT1, HK2 and LDHA,resulting in reduction in glycolysis. We further revealed that DPT-induced cell growth inhibition and increased glucose and lactate levels could be reversed by overexpressing HIF-1α. Additionally, we found that DPT repressed NSCLC growth and GLUT1, HK2 and LDHA expression in vivo. Overall, this study suggested that DPT inhibited NSCLC growth by preventing HIF-1α-mediated glycolysis.